Research progress on the pathogenesis of acute lung injury in sepsis - WANG Qin，YU Xu，LI Qingying，LU Yibin (Zhongguo linchuang yanjiu)
Sepsis is a systemic inflammatory response syndrome caused by severe infection leading to host dysfunction，often involving multiple organs and causing functional failure. Acute lung injury is the most common complication of sepsis，with high mortality.Although the research on acute lung injury in sepsis has been continuously deepened in recent years，its pathogenesis is not yet very clear. It may involve inflammatory responses，oxidative stress，genetic mechanisms，pyroptosis，mitochondrial autophagy，ferroptosis，abnormal coagulation，etc. This article reviews the research on the pathogenesis of acute lung injury in sepsis，with the aim of improving the systematic clinical understanding of this disease.